Analisis Historis Kebijakan Umar bin Abdul Aziz dalam Pengelolaan Zakat - Al Manaanu, Yusuf; Jamal, Mulyono; Nugroho, Triono; Muttaqi, Roqi (Tasamuh: Jurnal Studi Islam, 2023)
Umar bin Abdul Aziz (717 AD) is a caliph who should be remembered in history, especially in the management of zakat. During his leadership, zakat management underwent a very impressive reform. All types of assets owned by the people must be subject to zakat. The system and management of zakat were handled very professionally at that time. The types of assets and assets that are subject to zakat are becoming increasingly diverse. Umar bin Abdul Aziz was the first person obliged to issue zakat from assets from business income or service results, including salaries, honoraria, income from various professions, and various other mustafad malls. So, during his sovereignty, very abundant zakat funds were stored in Baitul Mal. Even the amil zakat officers find it difficult to find the poor who will be given zakat. Several factors influenced the success of zakat management and management during the time of Umar ibn Abdul Aziz. First, there is mutual awareness and maximum empowerment of Baitul Mal. Second, the responsibility of a leader is supported by the awareness of the people in creating solidarity, welfare, and empowerment among the people. Third, awareness of muzakki (zakat payers) who are relatively capable materially and have high loyalty for the benefit of the people.